Vendilly - Chain of Smart Vending Machines - Imanov, Emil (ADA University, 2021)
The technology changes the way how people interact with the surrounding environment. Nowadays, business process automation reached up until the consumers' side, leaving the job to be completed by the machine, instead of a human being. At the same time, self-serving enables consumers to spend less time in the queues, people buy cheaper products, and they can reach to the services all day. Entrepreneurs could find the application of cutting-edge technologies, such as robots, artificial intelligence, extreme programming, and brought innovation to all spheres. One of the examples is the application of robots in cafés to serve people without servants. We would like to innovate further to use a vending machine not as just an analog to retail stores, but also as a full substitute to the restaurant or café. Our idea is to serve food and beverages to people in business centers, shopping malls, clinics, and universities. We plan to import vending machines of the Necta brand, which is a very innovative company in the vending machine industry. Their devices comply with all required international health and safety standards, which can securely keep food and beverages in healthy condition. The objective of this business plan is to analyze the self-serving industry opportunity and apply it in the real world. The future company’s name is going to be Vendilly, since our strategic product will be coffee of Illy brand and the machines will be branded by the same brand. The target audience can be anyone who will be in the area where our machines are installed. The devices will be connected in closed places, near to the canteen or cozy zones. Consumers will be able to take the product with themselves or have a seat and enjoy their meal and drink.
Keywords: Business; Vending machines.; Vending machines -- Azerbaijan.; Self-serving industry.; Self-serving industry -- Azerbaijan.